UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII3 SMP NEGERI 32 PEKANBARU MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN THINK PAIR SQUARE (TPS) - Riani Octavianty Raju; Zulkarnain '; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and improve the student’s mathematics learning outcomes through the implementation of Cooperative Learning with Think Pair Square Approach. The type of research is the Classroom Action Research with two cycles. The research was conducted in studentof grade VII3 SMP N 32 Pekanbaru in the second semester of the 2015/2016 academic year with the subject of as many as 41 students. The research instrument are consists of learning devices and instrument data collectors. Learning device used in this research are consists of the Syllabus, Lesson plan and Student work sheet. The instrument data collector used in this research is consists of the observation sheet and math test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. Based on the result of the research show that, the learning process has improved and the student’s mathematics learning outcomes have improved after applying the Cooperative Learning with Think Pair Square Approach. The Cooperative Learning with Think Pair Square Approach can be used as an alternative in learning, because it can improve the learning process and improve the students learning outcomes.Keywords: Cooperative Learning, Think Pair Square Approach, learning process, students